About the Cover Image. (1st September 2021) - Joy, Phillip
Abstract : This image, Challenging Masculine Constructs by Oliver, is part of a photovoice project (see the article by Phillip Joy, Matthew Numer, Sara F. L. Kirk, and Megan Aston, Embracing a New Day: Exploring the Connections of Culture, Masculinities, Bodies, and Health for Gay Men through Photovoice, this issue) that explored the way culture and society shape the beliefs, values, and practices about food and bodies for gay men. Taken by the participant, this image is his way to challenge what he believes are limiting gender ideas for men and how masculine bodies should be dressed and presented to others. He disrupts these social constructs by dressing and presenting his body in ways he believed moved beyond typical masculine notions and by doing so reveals alternative gender expressions and new possibilities of living.